Performance analysis on handover for wlan 802.11b - Lee, L.W (Universiti Malaysia Sarawak, UNIMAS, 2010)
This project is to simulate the handover process of IEEE 802.11b by using Network Simulator-2. The main objectives of this project are to analyze the end-toend delay, throughput and jitter of IEEE 802.11b handover process. The simulation is conducted using different packet size (500 bytes, 1000 bytes and 1500 bytes) and using different transmission power of antennas. The antennas are set to different coverage which are 100 m and 250 m coverage. By using different transmission power of antennas and different packet size, the handover process can be observed and the effect of packet sizing are to be monitored in this simulation. The simulation environment in this project is 2 wired nodes, 2 access points and 1 mobile node connected in hierarchy. The mobile node is set to move from the first access point to the next access point at the speed of 10 m/s. From the project, it is found that the packet size of 1000 bytes show the fastest handover to the next access point as compared to packet size of 500 bytes and 1500 bytes. In addition, the end-to-end delay, throughput and jitter is found to produce much higher values as the packet sizing increases.